HIV surveillance in needlestick accidents with health workers - doi: 10.5020/18061230.2010.p325 - Janete Lane Amadei; Carina Ivatiuk (Universidade de Fortaleza, 2012)
Objective: To characterize the occurrence of needlestick accidents with health professionals submitted to rapid HIV tests. Methods: A descriptive, epidemiological study, carried out by notification of the occurrence of needlestick accidents in the Epidemiology Sector of the State Health Secretariat, in 2008. The following variables were assessed: gender, age, exposed biological material, type of exposure, source patient, and injured patient, progression of the case, accident situation, and use of personal protective equipment (PPE), 180 days serology and occupational area. Results: There have been reports of 143 accidents, prevailing in nursing, female, 20 to 30 years, involving the blood and biological material by percutaneous puncture. We found no standardization in the use of PPE. The HIV test revealed no positive cases. Conclusion: This study helped to characterize the occurrence of accidents reported in health care professionals and evaluate the protocol of care given. It also revealed non-contamination by HIV.